When I found you - Hyde, Catherine Ryan. (Las Vegas, NV : Amazon Publishing, 2013)
Nathan McCann thought he didn't want a family. But when he finds an abandoned newborn in the woods, he feels an inexplicable bond with the boy and starts to make plans to raise the child as his own--until the baby's grandmother steps forward to claim him.
Keywords: Abandoned children -- Fiction; Adopted children -- Ficiton; Widowers -- Fiction; Parent-child relationships -- Fiction